'It's my dream come true': experiences and outcomes of an inclusive dance talent development programme. (10th December 2019) - Aujla, Imogen J.
Abstract : There are few opportunities for young disabled dancers to develop their talents, and even fewer studies investigating their experiences of such opportunities. The aim of this study was to explore the perspectives and outcomes of an inclusive talent development programme, and how these were facilitated. Semi‐structured interviews and focus groups with one teacher, four young dancers and four parents revealed that participation in the programme yielded multiple benefits for the young people involved. These included high levels of enjoyment, improved technical and creative ability, greater independence and confidence, and opportunities for socialising with like‐minded peers. A range of factors facilitated these benefits, such as the inclusive and caring ethos of the programme, its comprehensive development and teacher training, particular teaching strategies, and relationships between staff, students and parents. The study attests to the value of programmes designed for young disabled dancers who wish to develop their talents.